An Empirical Analysis of Land Degradation Risk from Local Community Knowledge Perspective: The Case of Geze Gofa District, Southern Ethiopia. (Global Journal of Science Frontier Research, 2017)
Land degradation is increasing in severity and extent in many parts of the world Success in arresting land degradation entails an improved understanding of its causes process indicators and effects Various scientific methodologies have been employed to assess land degradation globally However the use of local community knowledge in elucidating the causes process indicators and effects of land degradation has seen little application by scientists and policy makers Land degradation may be a physical process but its underlying causes are firmly rooted in the socio-economic political and cultural environment in which land users operate Analyzing the root causes and effects of land degradation from local community knowledge perception and adapting strategies perspective will provide information that is essential for designing and promoting sustainable land management practices This study was conducted in Geze Gofa district southern Ethiopia The main objective of the study was to analyze land degradation risk from local knowledge perspective The study followed a multistage sampling procedure to select the sample respondent households for study The sample size of the study was 156 households The study was conducted using semi-structured interview schedule key informant interviews focus group discussions and field observation as a primary data collection techniques The data analysis for this study was conducted using both qualitative approaches thematically and quantitative approach- descriptive statistics and logistic regression analyses
Keywords: land degradation; local knowledge; farmersFFFD; perception; conservation measures